Smooth muscle cells in human atherosclerotic plaques express the fractalkine receptor CX3CR1 and undergo chemotaxis to the CX3C chemokine fractalkine (CX3CL1). - Lucas, A; Bursill, C; Guzik, T; Sadowski, J; Channon, K; Greaves, D (2003)
BACKGROUND: Chemokines are important mediators of inflammatory cell recruitment that play a significant role in atherosclerosis. Fractalkine (CX3CL1) is an unusual membrane-bound chemokine that mediates chemotaxis through the CX3CR1 receptor. Recently, functional polymorphisms in the human CX3CR1 gene have been described that are associated with coronary artery disease. METHODS AND RESULTS: We investigated the expression of the CX3C chemokine fractalkine and its receptor CX3CR1 in human coronary artery plaques by immunocytometry. We show that a subset of mononuclear cells expresses high levels of fractalkine in human coronary atherosclerotic plaques and that smooth muscle cells within the neointima express the fractalkine receptor CX3CR1. There is a positive correlation between the number of fractalkine-expressing cells and the number of CX3CR1-positive cells in human atherosclerotic plaques (r=0.70, n=15 plaques). Furthermore, we demonstrate that cultured vascular smooth muscle cells express the CX3CR1 receptor and undergo chemotaxis to fractalkine that can be inhibited by G protein inactivation by pertussis toxin. CONCLUSIONS: These results suggest that in human atherosclerosis, fractalkine, rather than mediating inflammatory cell recruitment, can act as a mediator of smooth muscle cell migration.